ANALISIS PENGELOLAAN DAN PERTANGGUNGJAWABAN ANGGARAN PENDAPATAN DAN BELANJA DESA - Pangemanan, Sintiya Febriany Debora (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2024)
The aim of this research is to analyze the management of the Village APBD in Wangeotak Village, Malifut District, North Halmahera Regency, and analyze APBDesa Accountability in Wangeotak Village, Malifut District, North Halmahera Regency. This research describes village financial management in Wangeotak village, Malifut sub-district which includes: planning, implementation, administration, reporting, accountability, guidance and supervision of village finances as well as comparing their conformity with Minister of Home Affairs regulation number 113 of 2014 concerning village financial management. The data used primary data, direct interviews with parties related to financial management and secondary data on the APBDesa, RPJMDesa, and RKPDesa. Research result show that management of village funds, the Wangeotak village government has carried out good management by referring to regulations or standards determined by the government. Good Village Fund Management is Regulated in Law Number 6 of 2014 concerning Villages, especially in Wangeotak village regarding Participation by involving the community in planning and transparency to provide open information in the implementation of the Wangeotak village fund in 2023 which has not been fully felt or known by the community as a whole due to because the transparency model is very confusing to find out how much budget will then be budgeted for 2023, which is in accordance with each field. The lack of participation from the community was also caused by political differences that occurred in 2019 related to the village elections.